EXPERIENCE OF FOREIGN COUNTRIES IN INCREASING INVESTMENT CAPACITY IN THE REGION (Marketing Journal, 2025)
This article examines the foreign experience of enhancing regional investment potential. Particular attention is paid to institutional mechanisms, investment promotion tools, and the formation of a favorable investment climate in developed and emerging eco nomies. The study systematizes effective approaches to increasing regional investment capacity and substantiates the possibility of their application in national economic conditions. The findings contribute to the development of methodological and practica l recommendations for strengthening regional investment attractiveness.
Keywords: investment potential; regional development; investment attractiveness; institutional factors; foreign experience; investment climate; economic development. 298